Magnet science - Vecchione, Glen (Scholastic Inc., 1995)
"Relates the discovery of magnetism, discusses the principles behind it, and suggests experiments which offer a "hands-on" explanation of how it works."
Terminologický slovník
Obsahuje rejstřík
Keywords: magnetismus; fyzikální pokusy; magnetism; physical experiments; publikace pro mládež; juvenile literature